Kangkilo Oral Tradition: Basic Multicultural Local Wisdom from Butonese to Create the Peace of The Nation - Arafah, Nur; Udu, Hamiruddin; Hidrawati, Hidrawati (Jayapangus Press, 2025)
Some traditions have values to glue the community live together in peace. However, many people especially young generations forgot it. This study aims to describe the basic multicultural local wisdom of the Buton people. The design of the research is a descriptive study by using qualitative descriptive method analysis. The results of the study showed that some local wisdoms in oral tradition of kangkilo were the basis for the creation of multicultural attitudes and understanding in Butonese. The values teach the community to protect themselves from chastity, both religious holiness and social holiness. Thus, people who understand this tradition will be obedient in following the teachings of their religion, and socially they will avoid attitudes and words that hurt other people's hearts, prevent heinous and unjust, treacherous, destructive acts, otherwise the values in tradition invite people to do good.